Use of the pedicle carpal pad for reconstruction of metacarpal pad defects in dogs - Gunay, Cihan; Sagliyan, Aydin; Ozer, Songul (My University, 2009)
A technique of carpal pad transposition applied to 12 dogs with experimentally induced metacarpal defects is described and illustrated. At 6 months following surgery, the transpositioned carpal pad was observed to have accommodated well with the region without any problem. It is concluded that carpal pad transposition is an adequate weight-bearing graft for the resconstruction of the defects observed on the metacarpal pad in dogs.
Keywords: Canis familiaris